2001
DOI: 10.1089/108076801753266811
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Receptor Binding and Signal Transduction Pathways of Unoprostone Isopropyl

Abstract: We examined the binding characteristics of unoprostone isopropyl and its metabolite, M1 (M1), in bovine corpus luteum membranes, mobilization of intracellular calcium in human ciliary muscle cells and cyclic AMP generation in rabbit iris-ciliary body. The ligand binding assay of 3H-unoprostone isopropyl and M1 did not demonstrate any specific binding of these compounds in the bovine corpus luteum membranes. However, there was a high specific binding of prostaglandin F2alpha. Competitive ligand binding studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…However, given our findings that unoprostone isopropyl and unoprostone free acid have micromolar binding affinities, we feel it would be difficult to detect appreciable specific binding using nanomolar concentrations of this weak radioligand. Bhattacherjee et al (2001) also reported that unoprostone failed to mobilize [Ca 2ϩ ] i in primary human ciliary muscle cells. We have found that [Ca 2ϩ ] i mobilization in response to FP prostaglandins in human ciliary muscle can be quite weak and donor dependent, perhaps suggesting that low receptor expression and/or poor signal coupling in these primary cultures may contribute to the lack of response observed with weak FP agonists.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, given our findings that unoprostone isopropyl and unoprostone free acid have micromolar binding affinities, we feel it would be difficult to detect appreciable specific binding using nanomolar concentrations of this weak radioligand. Bhattacherjee et al (2001) also reported that unoprostone failed to mobilize [Ca 2ϩ ] i in primary human ciliary muscle cells. We have found that [Ca 2ϩ ] i mobilization in response to FP prostaglandins in human ciliary muscle can be quite weak and donor dependent, perhaps suggesting that low receptor expression and/or poor signal coupling in these primary cultures may contribute to the lack of response observed with weak FP agonists.…”
Section: Discussionmentioning
confidence: 96%
“…In our hands, bimatoprost readily bound to the FP receptor and displaced [ 3 H]travoprost acid and [ 3 H]PGF 2␣ (this study). Bhattacherjee et al (2001) found no specific binding of unoprostone isopropyl ester or unoprostone using […”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Akin to the claims for bimatoprost (8,51), unoprostone has been suggested to mediate its actions via non-prostaglandin receptors (53,54). However, our studies have clearly demonstrated unopros- 137 6 10%** (160 6 11 at 1 nM)** (6)-Fluprostenol 131 6 6%** (162% at 1 mM)** PGE 2 118 6 6%*** S-1033 115 6 6% (200% at 10 mM) Unoprostone (UF-021) 105 6 4%*** (125% at 10 nM)** PGI 2 87 6 4%*** Comparative data for the PG analogs were obtained for MAP kinase stimulation in normal h-CM cells using a 5 min incubation paradigm.…”
mentioning
confidence: 99%